Analisis Kestabilan Model Penyebaran Penyakit Tungro Pada Tanaman Padi Melalui Vektor Wereng Hijau (Nephotetix Virescens) - Landita, A; Ratianingsih, R; Nacong, N (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2020)
ABSTRACT Tungro is a disease of rice plant (Oryza sativa) caused by tungro rice plant virus called Rice Tungro Baciliform Virus (RTBV) and Rice Tungro Spherical Virus (RTSV). Those viruses are transmitted by green planthopper vector (Nephotettix virescens). Rice tungro virus, that attack at vegetative phase, could make the rice plant tiny. This research governs a tungro transmission model that consider the rate of growth, natural mortality and virus infection as parameters. The interaction between green planthopper vector and spider as the predator of it is also considered. The other one is the probability of successes contacts between the green planthopper vectors with the susceptible rice population and tungro infected rice. The model, that modified from Susceptible-Infected model, has two critical endemic points of, and The stability of both points are analyzed using linearity and Routh hurwitz criteria. To reach their stability, the first critical point requires the values of natural death of green planthopper vector that must bigger than natural death of rice plant and the second critical point requires the natural growth rate of the spider predator must smaller than its natural death. Keywords : Analysis of Stability, Routh-Hurwitz Criteria, Tungro